A Preliminary Study on Sinus Fungus Ball with MicroCT and X-Ray Fluorescence Technique. - Zidong Jiang; Kai Zhang; Wanxia Huang; Qingxi Yuan (PLoS ONE)
Background Sinus fungus ball, an accumulation of fungal dense concretions, is a common disease in practice, and might cause fatal complications or lead to death once converted into invasive type. Early preoperative diagnosis of this disease can lead to appropriate treatment for patients and prevent multiple surgical procedures. Up to now, the diagnostic criteria of sinus fungus ball have been defined and computed tomography (CT) scan was considered as a valuable preoperative diagnostic tool. However, the sensitivity of clinical CT is only about 62%. Thus, investigating the factors which influence sensitivity is necessary for clinical CT to be a more valuable preoperative diagnosis tool. Furthermore, CT scan usually presents micro-calcifications or spots with metallic density in sinus fungus ball. Previous literatures show that there are some metallic elements such as calcium and zinc in fungus ball, and they concluded that endodontic treatment has a strong correlation with the development of maxillary sinus fungus ball and zinc ion was an exogenous risk factor. But the pathogenesis of sinus fungus ball still remains unclear because fungus ball can also develop in other non-maxillary sinuses or the maxillary sinus without root canal treatment. Is zinc ion the endogenous factor? Study on this point might be also helpful for investigating the pathogenesis of sinus fungus ball. In this paper, we tried to investigate the factors which influence the sensitivity of clinical CT by imaging sinus fungus ball with microCT. The origin of zinc ion was also studied through elements test for different fungal ball samples using x-ray fluorescence technique. Methods Specimens including fungal ball material and sinus mucosa from patients confirmed by pathological findings were extracted after surgery. All fungal ball specimens came from sphenoid sinus, ethmoidal sinus and maxillary sinus with or without previous endodontic treatment respectively. All of them were imaged by microCT with spatial resolution up to 5μm to acquire three-dimensional structure, and then the heavy metal elements were detected with x-ray fluorescence spectrometer analysis. Result High concentration of zinc and calcium were detected in all fungal ball specimens compared to sinus mucosa membrane. Particles with different size varied from disperse to density, which have similar shape to the result of clinical CT but with different size, were found in three-dimensional reconstruction results of microCT. Conclusions Spatial resolution is an influent factor of clinical CT sensitivity for sinus fungus ball. Improving the resolution of clinical CT will help to improve its sensitivity. Besides iatrogenic endodontic materials, endogenous metal elements of zinc and calcium might associate with the growth of fungal ball and the micro-calcifications or spots with metallic density of CT imaging.